Resisting Crisis Surveillance Capitalism in Academic Libraries - Bignoli, Callan; Buechler, Sam; Caldwell, Deborah; McElroy, Kelly (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2021)
In this paper, we consider what we identify as crisis surveillance capitalism in higher education, drawing on the work of Naomi Klein and Shoshana Zuboff. We define crisis surveillance capitalism as the intersection of unregulated and ubiquitous data collection with the continued marginalization of vulnerable racial and social groups. Through this lens, we examine the twinned crisis narratives of student success and academic integrity and consider how the COVID-19 pandemic further enabled so-called solutions that collect massive amounts of student data with impunity. We suggest a framework of refusal to crisis surveillance capitalism coming from the work of Keller Easterling and Baharak Yousefi, identifying ways to resist and build power in a context where the cause of harm is all around and intentionally hidden.